Slow fashion or self-signaling? Sustainability in the fashion industry - Castagna, Ana Carina (2022)
Castagna, A. C., Duarte, M., & Pinto, D. C. (2022). Slow fashion or self-signaling? Sustainability in the fashion industry. Sustainable Production and Consumption. [Advanced online publication on 25 March 2022]. https://doi.org/10.1016/j.spc.2022.03.024